Cloudburst [videorecording (DVD)] - Fricker, Brenda; Dukakis, Olympia; Booth, Kristin, 1974-; Doucette, Ryan; Fitzgerald, Thom (Wolfe Video LLC, 2013)
Stella and Dot have been together for 31 years and have faithfully accompanied one another through life's ups and downs. Now in their seventies, Stella is hard of hearing and Dot is legally blind. Dotty's prudish granddaughter, Molly, decides the best place for Dot is a nursing home that will provide all the necessities. This forces Stella and Dot to make a bold decision: they will leave their hometown in Maine and make their way to Canada, where same-sex marriage is legal.